Gloss on the judgement of the Supreme Administrative Court of 21 October 2022, III OSK 4468/21 (concerning the provision of public information by a foundation) (Ius Novum, 2024)
In its judgement of 21 October 2022, III OSK 4468/21, the Supreme Administrative Court considered that a foundation is obliged to provide public information because, in accordance with Article 1 Act on foundations, it should accomplish socially and economically useful objectives that are in compliance with the interests of the Republic of Poland. These are objectives that should also be accomplished by public administration; thus, they are in fact the State’s objectives. In such a situation, the Court decided that the informative obligation of foundations that are not public law ones applies in fact to every aspect of their activities, which should be recognised as right, because the constitution-maker specified in Article 61 par. 1 Constitution of the Republic of Poland a very broad range of entities obliged to provide public information so that every field of the State’s activity is transparent.
Keywords: Supreme Administrative Court, public information, foundation, obligation to provide data